The effect of dialogic-practical work on secondary school students mechanics achievement - Belay, Ewonetu Bantie; Alemu, Mekbib; Tadesse, Mesfin (Momentum: Physics Education Journal, 2023)
This study aimed to examine the effects of dialogic-practical work on secondary school students‘ mechanics' achievement. It also examined whether the students‘ mechanics achievement would vary with achievement levels. A quasi-experimental pre- and post-test research design was used. The study participants were 91 students from two secondary schools in Bahir Dar town, Ethiopia. The treatment group conducted dialogic-practical work and the comparison group carried out recipe-based practical work. A 25-item Mechanics Achievement Test was used for data collection. A paired- and independent sample t-tests were performed to analyze the data. It was found that there was a statisitcally significant difference in mechanics achievement between the dialogic-and recipe-based practical work groups, t (76) = 7.80, p < .001, d= 1.76. It also indicated that the dialogic-practical work resulted more improvements in mechanics achievement of the different achievement levels as compared to the recipe-based practical work. This suggests that students who engaged in dialogic practical work enhanced their mechanics achievement more than students who simply follow prescribed recipes. It is important to raise physics teachers’ awareness about the benefits of dialogic-practical work to enhance students’ mechanics' achievement.